Etika Berbicara di Era Media Digital: Studi Maudhu'i terhadap Hadis-Hadis Tentang Bahaya Lisan - Nisa Muflihah; Hairul Hudaya (Pascasarjana Universitas Islam Negeri Sumatera Utara Medan, 2025)
In the digital era, the widespread use of social media has amplified both the opportunities and risks associated with verbal communication. Despite the convenience of instant messaging and online discourse, unethical speech and harmful expressions have become increasingly prevalent, raising concerns about moral conduct in virtual spaces. This study identifies a gap in existing literature, as previous research primarily focuses on general ethical guidelines without systematically linking Islamic teachings on speech to contemporary digital communication challenges. Employing a maudhu'i (thematic) approach to hadith analysis, the research examines prophetic traditions concerning the dangers of speech and the ethical boundaries of verbal expression. Through thematic synthesis, key hadiths were classified and interpreted to extract principles relevant to digital communication ethics. The findings reveal that prophetic guidance emphasizes restraint, accountability, and mindfulness in speech, which are directly applicable to online interactions. The study concludes that integrating these ethical principles into digital behavior can mitigate the risks of misinformation, slander, and verbal harm, providing a structured framework for responsible communication in the modern media landscape.